SISTEM PENDUKUNG KEPUTUSAN OTOMATISASI PLANNING WISATA BERBASIS WEBSITE DENGAN MENGGUNAKAN METODE DIJKSTRA - Eko Suryanto; Anton Setiawan Honggowibowo; Nurcahyani Dewi Retnowati (Compiler, 2013)
The application development of website that have a good progress from Website is very important in tourism field where website can promote the interesting and unique of tourism place for tourist. In tourism field website can be important if completed with superriority is tourism planning where tourist can plan their holidays effective and efficient. Dijkstra method is a graph search algorithm is used to solve the problem with a single source shortest path on a graph that produces a shortest path tree. The usage of dijkstra method in decision the tourism planning base website is appropriate because used to plan the holidays based on the route or the sorthest way that has been found by latitude and longitude counting which is very important to decide range from each place, so it can help the tourist.